Assessing Government Support and Sustainability among Marawi Siege Survivors: Insights from Barangay Boganga - Fuentes-Marquez, Michelle Rose (Future Science / FSH-PH Publications, 2025)
This study assessed the relationship between government support and sustainability among 266 Marawi siege survivors in Barangay Boganga. Using a descriptive-correlational design and Likert-based questionnaires, the study found that economic and social support were perceived as Neutral to Much Supportive. A statistically significant positive relationship was found between government support and sustainability (r = .35, p = .002). Findings suggest continued investment in social and economic programs is essential for long-term recovery.